MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS MELALUI STRATEGI BERMAIN AKTIF PADA ANAK TK B AISYIAH BUSTANUL ATHFAL 1 DENPASAR TAHUN 2016 - Fitri, Nidya; Hartini (Jurnal Sakinah, 2020)
Speaking is one of dominant language activity in human life. Generally this reasearch focuses on increasing English language ability through role play startegy in kindegarden TK B Bustanul Athfal I Denpasar 2016/2017 year. The purpose of this research is to describe increasing English language ability through role play strategy to kindegarden TK B Bustanul Athfal I Denpasar 2016/2017 year. Population of this research is kindegarden TK B 20 person with 13 boys and 9 girls then one teacher as subject of research. Analysis data uses quantitative descriptively. Research procedure uses two siclus by four steps repeatly are planning, action, observation, evaluation, and reflection. Based on result analysis conlcludes that without using role play strategy are kindegarden get unsatisfied grade. In learning process, English language ability through role play strategy has increased chirdren grade in quantity and quality. First siclus, children group have high level English speaking ability through role play startegy is 10 person (58,82%), Intermediate level is 10 person (41,18%). While, second siclus, high level is 17 person (8 8,23%), intermediate level is 3 person. kemampuan sedang ada 3 orang (11,77%). Average grade level is increased from 68,82 to 75,15.